Питання впровадження інновацій, щодо енергозбереження в виробництві - Мелень, Олена Валентинівна (НТУ "ХПІ", 2010)
It is important to value the basic directions of innovative development on energy policy that will balance the functioning and sustainability of domestic economic and ecological systems.
Keywords: розвиток інноваційний; політика енергетична; безпека енергетична; енергоефективність